A Work-Related Thyrotoxic Periodic Paralysis in A Worker Exposed to Heat Stress: A Case Report - Puji Lestari, Shanti; Mansyur, Muchtaruddin (UI Scholars Hub, 2023)
Thyrotoxic Periodic Paralysis (TPP) is an uncommon disorder, characterized by the triad of acute hypokalemia, muscle paralysis, and thyrotoxicosis. Attacks are typically transient, last hours to days, and may be triggered by many conditions, including exposure to heat stress in both indoor and outdoor activities. Indoor workers, especially those working around furnaces, ovens, smelters, and boilers, are at a higher heat stress risk, even higher risk if they have other individual factors such as obesity, dehydration, slower heat acclimation, consume certain medications and presence of underlying diseases. A 48-year-old man presented a sudden onset weakness in all four limbs, associated with admission blood hypokalemia and thyrotoxicosis. No history of either alcohol or high carbohydrate intake consumption, infection, trauma, or heavy exercise. He has been working as a chef in the food procurement unit at a hospital for 28 years, 6 hours/day, six days/week. The results of the heat measurement at the cooking area where he works revealed that the heat stress index was 31,9º C Wet Bulb & Globe Temperature (WBGT).